Simulasi Kinerja Enhanced Oil Recovery (EOR) dengan Polymer dan Solvent CO2 pada Sumur Injeksi di Lapangan Norne Segmen C - Arik; Eriska Eklezia Dwi Saputri (JSED, 2025)
The threat of an energy crisis driven by declining production from conventional wells and depleting global oil reserves can be mitigated through Enhanced Oil Recovery (EOR), which has the potential to increase production by 30-60%. This study evaluates the potential application of EOR using polymer and CO2 solvent injections in Segment C of the Norne Field, Norway. The primary objective of this study is to determine the recovery factor, observe the vertical and areal dynamics of oil saturation, and compare the effectiveness of both methods. Continuous injection simulations were applied to wells C-1H, C-2H, C-3H, and C-4H. The results indicate that the oil recovery factor from polymer injection in well C-2H reached 49%, outperforming both the CO2 solvent injection (46.45%) and the basecase scenario (46%). Meanwhile, the gas recovery factors for the basecase, polymer, and CO2 solvent were recorded at 70.50%, 61%, and 71%, respectively. Furthermore, fluid movement evaluation shows that polymer injection provides a more uniform areal sweep efficiency both macroscopically and microscopically, unlike the CO2 solvent, which is prone to segregation within the reservoir. In conclusion, the continuous polymer injection method demonstrates superior performance compared to continuous CO2 solvent injection in the Norne Field Segment C.